An Introduction to the Nasa East Pacific Origins and Characteristics of Hurricanes (Epoch) Field Campaign - Amber E. Emory; Matthew McLinden; Mathias Schreier; Gary A. Wick (Tropical Cyclone Research and Review, 2015)
ABSTRACT: Over the past five years, tropical activity in the East Pacific has increased, while declining in the Atlantic Basin. In addition, during El Niño years, warmer than average sea surface temperatures further increase the likelihood of tropical cyclone formation in the East Pacific. Hurricane field campaigns used the Ku-/Ka-band High-Altitude Wind and Rain Airborne Profiler (HIWRAP) radar on the Global Hawk (GH) unmanned aircraft, in GRIP (Genesis and Rapid Intensification Processes 2010), HS3 (Hurricane and Severe Storm Sentinel 2012-14), and the NOAA Sensing Hazards with Operational Unmanned Technology (SHOUT 2015-16) field campaigns. Although originally designed for the GH, the X-band high-altitude RADar (EXRAD) has yet to be integrated and flown on an unmanned aerial vehicle. EXRAD will provide data with less attenuation of signal over deep convection as well as better estimates of three-dimensional winds with its nadir-pointing beam. As part of the NASA Hand On Project Experience (HOPE) Training Opportunity, our team proposed to fly the AV-6 GH aircraft with the EXRAD radar, the High Altitude MMIC Sounding Radiometer (HAMSR), and NOAA Advanced Vertical Atmospheric Profiling System (AVAPS) dropsondes to investigate genesis and/or rapid intensification (RI) of an East Pacific hurricane by measuring both the environment and interior structures. Information on planned activities primarily focused on the EXRAD high-altitude radar integration for the July-August 2017 science flight will be presented.